Family Perceptions Toward Muslim Corpses Management of COVID-19 Patients in Padang City - Taufik Hidayat; Rika Susanti; Rahma Tsania Zhuhra (Universitas Andalas, 2021)
Dr. M. Djamil Hospital as a referral center of COVID-19 cases in West Sumatera has a COVID-19 protocol in managing the corpses of COVID-19 patients. This study explores factors that affect patient’s family perception toward procedures of handling COVID-19 corpses. We held a qualitative study with phenomenological design to explore the family perceptions toward Muslims corpses management of COVID-19. Ten deep interviews were conducted with the ones who had their family members died by probable or confirmed COVID-19 and the corpses were managed according to COVID-19 protocols. Data triangulation was accomplished via in depth-interviews with two mortuary officers in Dr. M. Djamil Hospital. Three main themes were identified are the corpse management in COVID-19 patients, contributing factors regarding burial procedure during the COVID-19 pandemic, and challenges in managing corpses of COVID-19 patients